Limites e possibilidades para a apicultura na região central do Estado de São Paulo - Paschoalino, Augusto [UNESP]; Fonseca, Sérgio Azevedo [UNESP]; Strazza, Mariane de Carvalho [UNESP]; Lorenzo, Helena Carvalho de [UNESP] (Universidade Federal de Santa Maria, 2014)
Beekeeping is recognized as promoter of assumptions and dimensions of sustainable development, supported by the triple bottle line – economic viability, social relevance and environmental prudence. Historically, it is strongly related with the central state of São Paulo. This work has as main objective to identify the profile of beekeeping in the this region, based on four municipalities (Araraquara, Descalvado, Rio Claro and São Carlos) in order to determine the main difficulties faced by beekeepersfor the sustainable development, pointing alternative interventions able to soften the effects of difficulties. It was used two different and complementary methodological strategies. The first one was a search with the databases (SEADE and IBGE) to obtain secondary data and quantitative regarding beekeeping in the region. The second one, it wasthrough field research with the beekeepers. The survey found that beekeeping in the region, presents an essentially familial and hereditary. Was also noticed the damage caused in the production, by limiting access to the region’s bee pastures and use of pesticides. In processing, it was found the extremely precarious conditions. At the institutional level, it was found the relative weakness of the beekeepers cooperatives, and the lack of support from local governments to consolidate activity.

A atividade apícola é reconhecida como promotora dos pressupostos e das dimensões do desenvolvimento sustentável, apoiando-se no tripé viabilidade econômica, relevância social e prudência ambiental. Tendo isso em vista, este trabalho tem por objetivo central identificar o perfil da apicultura na região central paulista, tomando por base quatro municípios (Araraquara, Descalvado, Rio Claro e São Carlos) a fim de constatar as principais dificuldades enfrentadas pelos apicultores para o desenvolvimento sustentá- vel da atividade, apontando alternativas de intervenções capazes de abrandar tais dificuldades. Para isso, foram utilizadas duas estratégias metodológicas distintas e complementares: uma pesquisa nos sites do SEADE e do IBGE para obtenção de dados secundários e quantitativos referentes à produção regional e uma pesquisa de campo junto aos apicultores. Este estudo constatou que a apicultura regional apresenta caráter essencialmente familiar e hereditário. Também foram constatados os danos causados na produção pela limitação do acesso a pastos apícolas regionais e pelo uso de agrotóxicos. No âmbito do processamento e da comercialização, percebeu-se uma grande precariedade das condições enfrentadas, além de uma relativa fragilidade das cooperativas e falta de apoio dos governos locais para a consolidação da atividade no que se refere ao âmbito institucional.
Limits and possibilities for beekeeping in Central São Paulo State
Keywords: Beekeeping; Honey production; Sustainable local development; Public policy for local development; Apicultura; Produção de mel; Desenvolvimento local sutentável; Política pública de desenvolvimento local